2022
DOI: 10.3390/ani12070907
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Extract from Artemisia argyi Leaves on LPS-Induced Mastitis in Mice

Abstract: In the context of the unsatisfactory therapeutic effect of antibiotics, the natural products of plants have become a research hotspot. Artemisia argyi (A. argyi) is known as a traditional medicine in China, and its extracts have been reported to have a variety of active functions, including anti-inflammatory. Therefore, after establishing the mouse mastitis model by lipopolysaccharide (LPS), the effects of A. argyi leaves extract (ALE) were evaluated by pathological morphology of the mammary gland tissue, gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…For instance, Welz et al [ 64 ], showed that dissatisfaction with conventional treatment was the most important reason for use of herbal remedies. There are many reported cases of conventional drug failures due to drug resistance [ 12 , 65 ]. Of late, a lot of scientific investigations have been carried out on herbal medicine confirming their efficacy in certain conditions hence the several phyto-pharmaceutical products on the market [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Welz et al [ 64 ], showed that dissatisfaction with conventional treatment was the most important reason for use of herbal remedies. There are many reported cases of conventional drug failures due to drug resistance [ 12 , 65 ]. Of late, a lot of scientific investigations have been carried out on herbal medicine confirming their efficacy in certain conditions hence the several phyto-pharmaceutical products on the market [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence supported that neuroinflammatory mechanisms are involved in the pathogenesis of neurodegenerative disorders like AD. Induction of inflammatory conditions by an exogenous stimulant like LPS is well studied and it has been described that LPS administration alleviates the level of pro-inflammatory mediators and other cytokines ( 51 , 52 ). The release of these inflammatory cytokines like TNF-α, IL-1β, NOS-2, and prostaglandins are the intermediary mediators to induce neuronal injury and apoptosis ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that various extracts of A. argyi possess antioxidant, antibacterial, and immunomodulatory properties [ 7 , 44 , 45 ]. A previous study suggested that A. argyi water extract plays a positive role in lipopolysaccharide-induced oxidative stress by restoring the activities of GPx and SOD, and preventing the increase in nitric oxide concentration caused by the over-activation of total nitric oxide synthase [ 46 ]. Consistent with these results, the present study showed that A. argyi water extract significantly increased hepatic PON, GR, and GPx activity and decreased hepatic TBARS levels.…”
Section: Discussionmentioning
confidence: 99%